The river : peoples and histories of the Omo-Turkana area - Clack, Timothy; Brittain, Marcus (Archaeopress Publishing Ltd, 2018)
This sumptuously illustrated work brings together a remarkable collection of the world's leading archaeologists, ecologists, historians and ethnographers who specialise in the Omo-Turkana area (spanning spans parts of Ethiopia, South Sudan and Kenya), and recognising it as a crucial, and currently vulnerable, resource of global heritage.